IMPLEMENTATION OF ECOLOGICAL ARCHITECTURE IN WONOSOBO ZOO DESIGN - bagas; Hermawan Hermawan; Muafani (Clean Energy and Smart Technology, 2023)
Lack of animal habitats in nature caused by several human activities such as logging, hunting and land conversion causes animals to lack places to live, which in turn results in a decline in wildlife. At this point conservation efforts are made in order to save animals from extinction. Zoos are a type of ex-situ conservation effort that can be a forum for interaction between humans and animals, so that humans can learn about animals and build close relationships with animals. On the other hand, the zoo can also be a tourist attraction so that it can become an asset for the region to develop its tourism. Referring to these matters, planning a zoo in Wonosobo Regency can become a place for animals and become a new tourist attraction while still paying attention to ecological factors so that it continues to provide comfort for humans and animals in it and does not damage the surrounding environment.